Global Classroom Sessions enhance interpersonal effectiveness in diversity - Amy Zulaikha, Mohd Ali; Abdul Jalil, Abdul Rahim; Ruhil Amal, Azmuddin (UMPSA, 2024)
In the ongoing effort to enrich the academic experience of students in UHE3152 Interpersonal Effectiveness, an elective course offered by the Centre for Modern Languages (CML), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), the Global Classroom sessions continue to showcase a rich tapestry of perspectives on diversity.